Effect of 3, 4‐diaminopyridine at the murine neuromuscular junction. Issue 2 (17th August 2016) - Ng, Fiona; Lee, Diana C.; Schrumpf, Leah A.; Mazurek, Mary E.; Lee Lo, Victoria; Gill, Sharleen K.; Maselli, Ricardo A.
ABSTRACT: Introduction : We investigated the effects of 3, 4‐diaminopyridine (3, 4‐DAP) and its acetylated metabolite, N‐(4‐amino‐pyridin‐3‐yl) acetamide (3‐Ac), at the mammalian neuromuscular junction. Methods : Quantal release of acetylcholine was studied in diaphragm muscles of mice, using in vitro intracellular microelectrode recordings. Results : Under conditions of low probability of release, 3, 4‐DAP produced a 1, 000% increase in quantal release, but 3‐Ac had no effect. Under conditions of normal probability of release, the effect of 3, 4‐DAP was modest and limited by concurrent depletion of synaptic vesicles, especially with high concentrations of 3, 4‐DAP and high frequencies of nerve stimulation. Conclusions : These findings predict 3, 4‐DAP is most effective in conditions with low probability of quantal release, such as Lambert‐Eaton myasthenic syndrome. A beneficial effect is also expected in disorders of neuromuscular transmission in which the effect of 3, 4‐DAP on quantal release is not limited by depletion of synaptic vesicles, such as postsynaptic congenital myasthenic syndromes. Muscle Nerve, 2016 Muscle Nerve 55 : 223–231, 2017